The Use of Portfolio to Improve Translation Ability of English Department Students in State Polytechnic of Padang - Dhini Aulia; Desi Yulastri; Indah Sari (Universitas Negeri Padang, 2014)
A portfolio is a purposeful collection of students’ work that exhibit the students’ effort, progress, and achievement in one area. It can be useful media for both teacher and students or for the institution in order to see the progress and achievement in teaching learning process. This paper will discuss the use portfolio by students that is useful in order to improve their ability in translation. As one of compulsory subjects in English Department, Translation must be comprehended both in theory and practice. A research about the use of portfolio has been conducted in English Department, State Polytechnic of Padang. It was studying about the use of portfolio to improve the students’ translation ability. It proposed an alternative hypothesis that the use of portfolio would improve the translation ability of English Department students in the State Polytechnic of Padang. An experimental research design was conducted to prove the hypothesis above. It was found that tehere were significant progress getting by Experimental Group which got the treatment. The use of portfolio could help students to manage their assignments and the material related to the subject. It showed that the experimental group of students who used the portfolio got higher score in post test than the control group.